Tendon-inerter-damper helicopter blade augmentation for improved dynamic performance. (17th March 2023) - Jayatilake, Sanuja; Wu, Jun; Titurus, Branislav
Highlights: The model a blade with an internal tendon with inerter-damper (ID) guides is presented. Mode targeted tuning processes to obtain inertance and damping levels are discussed. Improved levels of modal damping obtained for a reference blade is illustrated. Device performance in off-design conditions (e.g., varying RPMs) are discussed. Squeeze film dampers (SFD) are discussed in the context of realising the ID guides. Feasible sizing solutions for SFDs within the blade's geometrical constraints are presented. Abstract: A novel helicopter blade concept with an adjustable tendon internally supported by dynamically tuned squeeze film damper guides is proposed to suppress the resonant blade vibrations. A physics-based representation of the tendon guides equivalent to an inerter-damper connected in parallel is further adopted to develop a new integrated blade-tendon-device model. The concept is then studied in terms of its optimal dynamic tuning characteristics and damping augmentation potential. The study is focused on single and multi-modal tuning performance in the context of a variable speed rotor with realistic pre-twisted blades used in modern light weight class helicopters. Initially, the significance of modal veering, non-local modes and eigenvalue merging under control parameter variations which include tendon tension, device damping, inertance and span-wise location is elucidated. Across the two separate two-mode optimal tuning studies, it is shown that the typical nominal levels of 0.5–2.0% of the blade modal damping arising from the structural sources can be significantly increased, for instance to 4.3% in case of the second in-plane blade mode and 13.4% in case of the second out-of-plane blade mode. After performing the conceptual device sizing study under realistic constraints utilising the optimal tuning parameters and an adopted squeeze film damping model, it is shown that the concept can be realised within the existing limits of the blade envelope. The proposed concept is shown to be robust and adaptive in its nature with the ability to introduce highly focused blade damping.